Requirements for the development of a social subjects curriculum in primary schools from the perspective of teaching board members (teachers). - محمد, م. د.مریم محمد ڕوستم (Sulaimani Journal for Humanities, 2025)
The main objective of this research is to “know the needs of developing the curriculum of social subjects in primary schools from the perspective of teaching staff members (teachers). The research included 309 teachers from both Eastern and Western Education Directorates in Sulaimani province. The sample consisted of 40 teachers randomly selected, including 20 teachers from Eastern Education Directorate and 20 teachers Western Education Directorate has determined both male and female. The researcher prepared the research tool based on previous readings and sources, in the form of an open survey, which consisted of four main topics such as (scientific content, teaching tools, classroom environment, assessment). (7) people in the field of teaching methods, expertise, assessment) After returning and collecting answers, the tool was approved by 78% (80%) was found, so began to implement the research, for the academic year (2023-2024) AD, after the end of the research experiment, statistical equations were used, such as Person's correlation coefficient, appropriate center, percentage weight The study concluded with a number of recommendations.